Risk factors analysis of constipation in patients with acute coronary syndrome. (April 2020) - Zukhri, S; Setianingsih,; Hastuti, R Y; Setyaningsih, I
Abstract: Pathophysiologically, patients with the acute coronary syndrome (ACS) are at risk of constipation. This study was aimed to determine the relationship of age, fluid intake, fiber intake, use of sedatives, and mobilization status with the occurrence of constipation in patients with ACS in intensive care unit (ICU). Thirty ACS patients (21 male and 9 female, aged 45 to 74 years who were treated in the ICU of PKU Muhammadiyah Delanggu Hospital, Klaten, Indonesia, in November - December 2018, were observed for 3 consecutive days from the initial admission to ICU. Data were analysed with the binary multiple logistic regression tests at 95% confidence level. Multivariate analysis showed that fiber intake (p=0.025, RR=26.675, CI 95%= 1, 498-474.996), fluid intake (p=0.044, RR=21.332, CI 95%= 1, 093 –416.328) and immobilization (p= 0.012, RR = 15.466, 95% CI =1.068-349.989) were significantly correlated to the occurrence of constipation with Negelkere R2 = 0.80, whereas age and used of sedative were not. It was concluded that lack of fiber intake, lack of fluid intake, and immobilization were the risk factors for the occurrence of constipation in ACS patients and contributed of 80.3% the occurrence of constipation in ACS patients, whereas of 19.7 % influenced by other factors were didn't study in recent research. However further research needed to be done with a larger of sample size.